ANALYSIS OF WEATHER WITH DENGUE HEMORRHAGIC FEVER IN BANYUWANGI DISTRICT, INDONESIA - Ristanti, Dyah (International Journal of Public Health Science (IJPHS), 2020)
Dengue hemorrhagic fever is an infectious disease caused by the vector of the mosquito Aedes aegypti carrying the dengue virus with the fastest spread of the disease in the world. Cases of dengue hemorrhagic fever have an increase of 1,817 cases spread in East Java Province. From 2012 to 2016 there were the highest cases of 214 cases in the Banyuwangi District. The purpose of this research is to analyze the weather against dengue hemorrhagic fever in Banyuwangi District in 2012-2016. Quantitative research is descriptive study using time series ecology study design. This study uses univariate analysis to provide an overview of the weather and the incidence of dengue hemorrhagic fever. Statistical analysis used correlation analysis to obtain the relationship between weather variables and the incidence of dengue hemorrhagic fever. The results of the study showed that the incidence of DHF occurred at the age of <15 years compared to the adult age of ?15 years. Correlation test results between weather variables including temperature (r = 0.339), humidity (r = 0.927), rainfall (r = 0.142) and sun irradiation time (r = 0.259) showed that there was a relationship with the incidence of DHF. Rainfall variable is a variable that has the strongest relationship with the incidence of DHF. The community can anticipate the prevention of dengue fever at the beginning of the rainy season and the end of the rainy season, by using preventive methods against mosquito bites using rapellent during the day.